Tingkat Kepuasan Pasien BPJS Rujuk Balik pada Pelayanan Kefarmasian di Apotek Kimia Farma Slamet Riyadi Sukoharjo - Nisa, Qoyyimatun; Hartono, H (Indonesian Journal on Medical Science, 2024)
Pharmaceutical care and patient satisfaction are the orientation of pharmaceutical services that must be carried out by pharmacies. To ensure the quality of pharmaceutical services in pharmacies, it is necessary to evaluate the quality of pharmaceutical services continuously. Kimia Farma Slamet Riyadi Sukoharjo Pharmacy is a Reverse Referral Program pharmacy in collaboration with BPJS Health from 2019 until now. This study aims to determine the level of satisfaction of BPJS Referral patients on pharmaceutical services at the Kimia Farma Slamet Riyadi Sukoharjo pharmacy as a self-evaluation material to improve the quality of service to patients. This research is a descriptive study conducted through an observational survey of the satisfaction level of the Servqual model. The sampling technique was carried out using purposive sampling technique with inclusion criteria. Analysis of the results was carried out by calculating the score of patient satisfaction level obtained from the results of patient answers using a Likert scale. The results of the research on the level of satisfaction of BPJS Referral patients at the Kimia Farma Slamet Riyadi Sukoharjo Pharmacy in the tangible dimension with a score of 90% (very satisfied), the reliability dimension is 86% (very satisfied), the responsiveness dimension is 86% (very satisfied), the guarantee dimension is 82% (very satisfied) and the empathy dimension is 87% (very satisfied). Based on the five dimensions of satisfaction, it can be concluded that the BPJS Referral pharmaceutical service at the Kimia Farma Slamet Riyadi Pharmacy in Sukoharjo patients are very satisfied with a percentage of 86%.